Phosphorylations of the Abutilon Mosaic Virus Movement Protein Affect Its Self-Interaction, Symptom Development, Viral DNA Accumulation, and Host Range - Kleinow, Tatjana; Happle, Andrea; Kober, Sigrid; Linzmeier, Luise; Rehm, Tina M.; Fritze, Jacques; Buchholz, Patrick C. F.; Kepp, Gabi; Jeske, Holger; Wege, Christina (Frontiers in Plant Science, 2020)
The genome of bipartite geminiviruses in the genus Begomovirus comprises two circular DNAs: DNA-A and DNA-B. The DNA-B component encodes a nuclear shuttle protein (NSP) and a movement protein (MP), which cooperate for systemic spread of infectious nucleic acids within host plants and affect pathogenicity. MP mediates multiple functions during intra- and intercellular trafficking, such as binding of viral nucleoprotein complexes, targeting to and modification of plasmodesmata, and release of the cargo after cell-to-cell transfer. For Abutilon mosaic virus (AbMV), phosphorylation of MP expressed in bacteria, yeast and Nicotiana benthamiana plants, respectively, has been demonstrated in previous studies. Three phosphorylation sites (T221, S223 and S250) were identified in its C-terminal oligomerization domain by mass spectrometry, suggesting a regulation of MP by posttranslational modification. To examine the influence of the three sites on the self-interaction in more detail, MP mutants were tested for their interaction in yeast by two-hybrid assays, or by Förster resonance energy transfer (FRET) techniques in planta. Expression constructs with point mutations leading to simultaneous (triple) exchange of T221, S223, and S250 to either uncharged alanine (MPAAA), or phosphorylation charge-mimicking aspartate residues (MPDDD) were compared. MPDDD interfered with MP-MP binding in contrast to MPAAA. The roles of the phosphorylation sites for the viral life cycle were studied further, using plant-infectious AbMV DNA-B variants with the same triple mutants each. When co-inoculated with wild-type DNA-A, both mutants infected N. benthamiana Domin plants systemically, but were unable to do so for some other plant species of the families Solanaceae or Malvaceae. Systemically infected plants developed symptoms and viral DNA levels different from those of wild-type AbMV for most virus-plant combinations. The results indicate a regulation of diverse MP functions by posttranslational modifications and underscore their biological relevance for a complex host plant-geminivirus interaction.